Channel doping effects in negative capacitance field-effect transistors. (December 2021) - Liu, Baoliang; Huang, Xiaoqing; Jiao, Yanxin; Feng, Ning; Chen, Xuhui; Rong, Zhao; Lin, Xinnan; Zhang, Lining; Cui, Xiaole
Highlights: Channel doping effects of negative capacitance field-effect transistors (NCFET) are analysed. A physics-based model is formulated capturing the complex doping effects especially the non-monotonic dependence of threshold voltages. A statistical model for the variations of NCFETs current–voltage characteristics is developed for statistical circuit simulations. Abstract: The channel doping effects in negative capacitance field-effect transistors (NCFETs) of the metal-ferroelectric-insulator-semiconductor (MFIS) structure are analysed in this work, and an analytical model is developed. The NCFET threshold voltage with channel doping is defined, and a nonmonotonic dependence on the doping concentrations is predicted. A unified charge formulation is developed for the current–voltage characteristics of double gate MFIS structures. Statistical modelling for NCFETs is further developed. Standard deviations of four parameters are extracted, reproducing the distributions of NCFET current–voltage characteristics. Experimental calibrated TCAD simulations validate the analytical model for wide ranges of device parameters, allowing its application to devices and circuits.